Project Assessment with Nationalism Insight at Elementary Schools and Its Impact Towards Students’ Social Science Achievement and Nationalism Attitude - Widiana, I Wayan (LPPM Undiksha, 2022)
The low of social science learning outcomes occur because teacher tends to give tests that lead to cognitive assessments and only assess students’ attitudes when doing tests without paying attention towards student skills. This study aimed to analyse the effect of learning by applying a project assessment with a national perspective on social studies learning outcomes and students’ attitudes toward nationalism. The type of research was quasi-experimental design with a non-equivalent post-test-only control group. This study’s population was all class V students by total 231 students. The amount of sample in this study is 46 people. Data collection methods were test and non-test. Instruments of learning outcomes and attitudes of nationalism were then validated in content and empirically by two experts with item validity and reliability tests. The data collected were analysed using analysis with MANOVA. The study’s results based on the calculation of the MANOVA test obtained a significant number of 0.000 which means less than 0.05 (0.000 <0.05). It means that there are differences, either partially or simultaneously, in social studies learning outcomes and students’ attitudes toward nationalism who were taught by applying a project assessment with a national perspective. It is concluded that using project assessment with a national view positively affect social studies learning outcomes and the nationalism attitude of fifth grade elementary school students.